1997
DOI: 10.1093/bja/78.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of i.v. propacetamol, metamizol or external cooling in critically ill febrile sedated patients

Abstract: SummaryWe have measured the metabolic response to sequential administration of propacetamol, metamizol and/or external cooling in 20 febrile patients under sedation and analgesia and during mechanical ventilation. There was no change in temperature (TЊ) after propacetamol therapy, whereas after metamizol only a small decrease was noted (from 38.9 (SEM 0.2) to 38.5 (0.3) ЊC; P:0.02). External cooling produced a significant decrease in TЊ (39.1 (0.2) to 37.1 (0.2) ЊC; P:0.0001) accompanied by a decrease in energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 17 publications
2
50
1
2
Order By: Relevance
“…We found that cooling allows a decrease of almost 6 b/ min for each degree of temperature lowering. This is in accordance with previous physiological studies reporting a mean decrease of 7 b/min/°C when controlling fever by cooling in ICU patients [8,27].…”
Section: Discussionsupporting
confidence: 93%
“…We found that cooling allows a decrease of almost 6 b/ min for each degree of temperature lowering. This is in accordance with previous physiological studies reporting a mean decrease of 7 b/min/°C when controlling fever by cooling in ICU patients [8,27].…”
Section: Discussionsupporting
confidence: 93%
“…These cases have presented both with (21) and without (22) other symptoms of allergic reaction such as bronchospasm or generalized skin rash. Studies of intravenous metamizol in surgical or critically ill patients have shown variable cardiovascular effects, ranging from no significant differences versus comparison group(s) to transient hypotension (23)(24)(25)(26)(27)(28). In one series of critically ill, febrile patients, metamizol infusion reduced MAP by an average of 10 mmHg at two hours post-infusion, with recovery to baseline by four hours (24).…”
Section: Discussionmentioning
confidence: 99%
“…Cooling patients in the ICU provides physiologic benefit, reducing metabolic requirements (38,39). In a randomized clinical trial, Bernard and colleagues (10) evaluated the effect of intravenous ibuprofen on 455 septic patients.…”
Section: Original Researchmentioning
confidence: 99%